Urban security in Europe: Translating a concept in public criminology. (May 2013) - Edwards, Adam; Hughes, Gordon; Lord, Nicholas
A key challenge for public criminology is the translation between concepts employed in policy discourse and those used by social scientists. Given that concepts constitute social problems and they can have multiple meanings for policy-makers and social scientists, then deliberation about what they signify matters in understanding how these actors can talk to, rather than past, one another in framing policy discourse about crime and revealing alternative policy agendas. This challenge is accentuated in the comparative context of European criminology, which is characterized by competing tendencies to generalize about problems of 'Freedom, Security and Justice' and to recognize the variegated problems and cultures of control across Europe. In this context, the presumption of universality can mistranslate concepts of crime and control by obscuring contextual insight, while the presumption of particularity can inhibit cross-cultural dialogue and deliberation. The paper explores this challenge in relation to the concept of 'urban security', which is prevalent in the policy discourse on social crime prevention, particularly in Central and Southern Europe. To establish the provenance, prevalence and significance of this concept, the paper discusses findings from a policy Delphi that structured deliberation about the meaning of urban security among criminologists sampled from the European Society of Criminology and policy-makers sampled from the European Crime Prevention Network. It concludes with reflections on the value of deliberative methods, such as the policy Delphi, for the cross-cultural validation of criminological constructs in comparative research.